Fresno County DSS Director Ben Kelley Retirement Dinner at Holiday Inn - Watkins, Howard::::::::: (1989)
Headtable: Prudence Hutton, Dan Fitzpatrick, Ben Kelly and wife, Ramona Leila Hogner and Don Hogner